Mapping the scholarship on international students: A systematic review of past publication to the Journal of International Students (2011–2024) - Hong, Bawool; Bista, Krishna; Timmons, Patricia (Journal of International Students, 2025)
The Journal of International Students has published works by over 1,883 authors, reflecting a significant growth in contributions over its 14 volumes and 60 issues. These authors represent diverse geographical backgrounds, hailing from over 60 countries across North America, Europe, Asia, Oceania, and other regions, underscoring the journal's global reach and inclusivity. This systematic review examines the Journal of International Students (JIS) from 2011 to 2024, identifying key themes, methodologies, and geographic focuses of the published articles. The study highlights the evolution of JIS, the diversity of contributing authors, and the journal's impact on international education research. By analyzing recurring issues such as cultural adjustment, academic integration, and social support, the review provides insights into how JIS has contributed to the broader discourse on international students' experiences and challenges. The findings aim to guide future research directions and inform policies and practices in international education.